ANALYSIS OF SERVICE QUALITY ON PATIENT SATISFACTION IN INPATIENT INSTALLATIONS OF REGIONAL HOSPITAL 2024 - Khodijah, Rosni; Akhmad Dwi Priyatno; Syntia Rahutami (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Good service is not only measured by luxurious facilities, complete technology and physical appearance, employee attitudes and behavior must also show high professionalism and commitment. Quality of health services refers to the level of perfection of health services that makes every patient feel satisfied.  This study aims to determine factors related to service quality and patient satisfaction at the Inpatient Installation of Ogan Ilir District Hospital in 2024. Quantitative research design with a cross-sectional approach. The population in this study was 854 inpatients at the Ogan Ilir District Hospital. The sample in the research consisted of 90 respondents. The sampling technique uses purposive sampling, using the Slovin formula. This research was carried out on March 13 - April 17 2024. Data was collected using a questionnaire. Bivariate data analysis using the chi-square test and multivariate using logistic regression.  The research results show that there is a relationship between responsiveness (p value 0.005) and tangibles (p value 0.001). There is no relationship between reliability (p value 0.86), assurance (p value 0.76) and empathy (p value 0.96). The most dominant factor in patient satisfaction in the Inpatient Installation of Ogan Ilir District Hospital in 2024 is tangibles (p value 0.00), (OR 0.183).  The conclusion is that there is a relationship between responsiveness and tangible. Suggestions from the research results can provide input about the quality of service on patient satisfaction in the Inpatient Installation of the Ogan Ilir Regency Regional Hospital in 2024 and contribute to improving health services